2012
DOI: 10.1007/s13744-011-0010-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Industrial Anthropization on Mosquito (Diptera, Culicidae) Communities in Mangrove Areas of Guanabara Bay (Rio de Janeiro, Brazil)

Abstract: The effects of industrial anthropization on species composition and community diversity of Culicidae (Diptera) were studied in a mangrove area impacted by industrial activities as compared to a preserved area, both around Guanabara Bay in the state of Rio de Janeiro, Brazil. Diversity, equitability, and species richness in Culicidae community differed between the studied areas. Indicator species analysis and correspondence analysis were carried out and indicated that the Sabethini, especially Wyeomyia (Phoniom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The other selected article, de Souza et al (2012) had similar finding with Ismail et al (2018) that disturbed mangrove area had more difficult condition. De Sauza et al (2012) found that caught mosquito in undisturbed mangrove area were from Wyeomyia species, while caught mosquito in disturbed mangrove area were from Aedes species [15]. Wyeomyia is not related with any human diseases although several studies proved some viruses were found in it [1,18].…”
Section: Resultsmentioning
confidence: 99%
“…The other selected article, de Souza et al (2012) had similar finding with Ismail et al (2018) that disturbed mangrove area had more difficult condition. De Sauza et al (2012) found that caught mosquito in undisturbed mangrove area were from Wyeomyia species, while caught mosquito in disturbed mangrove area were from Aedes species [15]. Wyeomyia is not related with any human diseases although several studies proved some viruses were found in it [1,18].…”
Section: Resultsmentioning
confidence: 99%
“…were found to be present, while more than one species were found in undisturbed mangrove areas. 27 Another study also found that amount of industrial land and percentage of mangrove was positively related to mosquito abundance and mosquito species richness. 28 Until now, there has not been any proof yet of LF being found in swamp and mangrove environments.…”
Section: Swamps and Mangrove Environmentsmentioning
confidence: 96%
“…Several investigations found that undisturbed mangrove areas had more mosquitoes with mosquito biting patterns only in the dawn and dusk, while the disturbed mangrove had less number of mosquitoes with irregular biting pattern throughout the day. 27 In the undisturbed mangrove areas, particular species like Wyeomia sp. were found to be present, while more than one species were found in undisturbed mangrove areas.…”
Section: Swamps and Mangrove Environmentsmentioning
confidence: 99%